2008
DOI: 10.1530/eje-07-0169
|View full text |Cite
|
Sign up to set email alerts
|

Long-standing, insulin-treated type 2 diabetes patients with complications respond well to short-term resistance and interval exercise training

Abstract: Objective: To determine the feasibility and the benefits of combined resistance and interval exercise training on phenotype characteristics and skeletal muscle function in deconditioned, type 2 diabetes (T2D) patients with polyneuropathy. Design: Short-term, single-arm intervention trial. Methods: Eleven male T2D patients (age: 59.1G7.5 years; body mass index: 32.2G4.0 kg/m 2 ) performed progressive resistance and interval exercise training thrice a week for 10 weeks. Besides primary diabetes outcome measures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 84 publications
(95 reference statements)
3
67
1
1
Order By: Relevance
“…ES for each of the controlled trials was interpreted according to the method of Cohen [16]. from 18 studies including 3 randomized controlled trials reported in 9 publications [17][18][19][20][21][22][23][24][25] (2 trials reported in 8 publications with resistance training [17][18][19][20][21][22][23][24] and 1 with aerobic training [25]), 2 non-randomized controlled trials [26,27] (with aerobic training [26,27]) and 13 uncontrolled trials reported in 15 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (11 trials reported in 13 publications with aerobic training [28,[30][31][32][33][34][35][36][37][38]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ES for each of the controlled trials was interpreted according to the method of Cohen [16]. from 18 studies including 3 randomized controlled trials reported in 9 publications [17][18][19][20][21][22][23][24][25] (2 trials reported in 8 publications with resistance training [17][18][19][20][21][22][23][24] and 1 with aerobic training [25]), 2 non-randomized controlled trials [26,27] (with aerobic training [26,27]) and 13 uncontrolled trials reported in 15 publications [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (11 trials reported in 13 publications with aerobic training [28,[30][31][32][33][34][35][36][37][38]…”
Section: Discussionmentioning
confidence: 99%
“…In the randomized controlled trials and non-randomized controlled trials, all studies consisted of mixed gender cohorts [17][18][19][20][21][22][23][24][25][26][27]; in the uncontrolled trials, five studies published in six papers were in male cohorts [31,32,34,37,38,42], seven studies published in eight papers were in mixed cohorts [28][29][30]33,35,36,39,41] and one study did not report gender [40].…”
Section: Gendermentioning
confidence: 99%
See 3 more Smart Citations